2019
DOI: 10.1101/781393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defective excitatory/inhibitory synaptic balance and increased neuron apoptosis in a zebrafish model of Dravet syndrome

Abstract: Dravet syndrome is a type of severe childhood epilepsy that responds poorly to current antiepileptic drugs. In recent years, zebrafish disease models with Scn1Lab sodium channel deficiency have been generated to seek novel anti-epileptic drug candidates, some of which are currently undergoing clinical trials. However, the spectrum of neuronal deficits observed following Scn1Lab depletion in zebrafish larvae has not yet been fully explored. To fill this gap and gain a better understanding of the mechanisms unde… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…In humans suffering from acute OP intoxication, whenever neuronal hyperexcitation is not rapidly treated, epileptic seizures eventually develop into SE, a major life-threatening neurological condition 6,45 , which also causes long-term brain damage 46,47 . Interestingly, in the zebrafish model of OP poisoning presented here, we observed that almost all the larvae displayed numerous massive calcium transients from 2 to 3 h after DFP exposure onward, which were strongly reminiscent of those associated with generalized seizures seen in both genetic and pharmacological zebrafish epilepsy models 14,26 . Altogether, these findings strongly suggest that DFP exposure causes epileptiform neuronal hyperexcitation in zebrafish larvae, eventually leading to a status epilepticus-like condition.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…In humans suffering from acute OP intoxication, whenever neuronal hyperexcitation is not rapidly treated, epileptic seizures eventually develop into SE, a major life-threatening neurological condition 6,45 , which also causes long-term brain damage 46,47 . Interestingly, in the zebrafish model of OP poisoning presented here, we observed that almost all the larvae displayed numerous massive calcium transients from 2 to 3 h after DFP exposure onward, which were strongly reminiscent of those associated with generalized seizures seen in both genetic and pharmacological zebrafish epilepsy models 14,26 . Altogether, these findings strongly suggest that DFP exposure causes epileptiform neuronal hyperexcitation in zebrafish larvae, eventually leading to a status epilepticus-like condition.…”
Section: Discussionmentioning
confidence: 61%
“…Five dpf larvae from the transgenic line Tg[Huc:GCaMP5G] were treated with DFP or vehicle (DMSO) and calcium transients were recorded during the following 6 h using time-lapse confocal microscopy ( Supplementary Videos 1 and 2). Interestingly, in DFP-treated larvae, we observed numerous intense calcium transients, from approximately 1 h post-exposure onward, which were highly reminiscent of those seen in zebrafish genetic epilepsy models 14 . Moreover, these calcium transients were mostly seen in the neuropil region, where a large number of synaptic connections occur ( Fig.…”
Section: Dfp Exposure Induced Neuronal Hyperexcitationmentioning
confidence: 56%
See 3 more Smart Citations